THE EFFECT OF LAVENDER AROMATHERAPY TO DECREASE THE INTENSITY OF CHILDBIRTH PAIN IN THE FIRST STAGE (Studied in the health center of Blimbing Gudo district of Gudo Jombang regency) - Heny Nur Imawati; Sri Sayekti; Rizky Andika Putra (Jurnal Keperawatan, 2012)
The childbirth process begins at the time of regular and progressive uterine contractions and will end with the release of the fetus. That childbirth process is accompanied by pain. Childbirth pain especialy in first stage caused by the presence of uterine contractions which resulted in dilatation and thinning of the cervix on the uterus. That pain felt the mother during contraction and decrease or disappeared at intervals of contraction. The purposes of this research was to know the effect of lavender aromatherapy to decrease the intensity of childbirth pain in the first stage.This research was a quasy experiment with research design of pre- post test. The population in this research were 13 respondents. The total of sample in this research were 8 respondents. The sampling used Simple random sampling technique. The research instrument was used observation with a scale measuring pain NRS (Numerical Rating Scale). Data processing by editing, coding, scoring, tabulating and data analyzing used wilcoxon test.The research result obtained that the pain intensity before given lavender aromatherapy was all 8 (100%) respondents experienced heavy pain. The pain aftee given lavender aromatherapy was mostly 6 (75%) respondents got reduction of pain became moderate pain. The resuls of statistical test obtained value of ρ = 0,014, ρ < 0,05, so H1 accepted. Conclusion of the research results that there are the effect of lavender aromatherapy to decrease the intensity of childbirth pain in the first stage in the Health Center of Blimbing Gudo district of Gudo, Jombang regency.